Endoparasite in sheep / Aida Mastura Ahmad Anuar - Ahmad Anuar, Aida Mastura (2017)
Parasitism such as gastro-intestinal parasites in sheep is the main reasons of high percentage in mortality and morbidity if they are present in large number. It can cause production losses which include lowering the productivity of sheep, reduction of metabolic efficiency of the sheep and increasing the number of death in sheep. The aim of this study is to determine the occurrence of endoparasites especially nematodes and trematodes in sheep’s feces and to observe the morphology of endoparasites found in sheep’s feces. The morphology of the endoparasites such as the shape and size of the eggs or oocyts were determined by the microscopic examination using three different methods such as direct smear method, floatation method and sedimentation method. Results of nematodes from twenty samples around Negeri Sembilan area that have been examined are Chabertia ovina, Haemonchus contortus, Trichostrongylus sp., Strongyloides papillosus and Trichuris ovis. However, trematodes are not observed in this experiment. Further study on identification of endoparasite and using the McMaster chamber is recommended.